Online Brand Experience: Drivers and Consequences - Pratomo, Luki Adiati; Magetsari, Ovy Noviati Nuraini (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2018)
The purpose of this study is to determine the influence of brand involvement, customer-brand engagement, online brand experience to brand satisfaction and brand loyalty of mobile banking applications users in BCA, Bank Mandiri, BRI, and BNI as the big four most valuable brands in Indonesia. This study used primary data sources obtained directly by distributing questionnaires to 260 respondents. The sampling method used is non-probability sampling with purposive sampling technique, and the criteria of respondents used in this study are consumers who own and use mobile banking applications at least once a month. The research method used is SEM, analysis of data quality using a validity test and reliability test. The findings of this study are Brand Involvement has a positive effect toward Customer Brand Engagement, Customer Brand Engagement has a positive effect toward Online Brand Experience, Online Brand Experience has a positive effect toward Brand Satisfaction and Brand Loyalty. Brand Satisfaction has a positive effect toward Brand Loyalty.Â